Estimating financial integration in Europe: How to separate structural trends from cyclical fluctuations - Alfred Lake; Laurent Maurin; Enrico Minnella (European Investment Bank (EIB), 2022)
We construct a new indicator of de facto financial integration in the EU. The resulting indicator is pro-cyclical as it evolves along the cyclical pattern of economic activity in the European Union. It is then appended to a set of relevant financial and macroeconomic variables, within a FAVAR framework, to allow us to separate the impact of cyclical boom-bust shocks from structural integration shocks. Increasing structural financial integration tends to improve risk absorption and reduce income disparities among European countries. However, our analysis suggests that most of the movements in the indicator reflect business cycle dynamics, not proper integration. Given the estimated beneficial effects of stronger structural financial integration, these results highlight the need to develop further policies to foster it in the EU.
Keywords: E44; F36; F44; G15; 330; Business Cycle; FAVAR Models; Financial Markets; Macroeconomic Shocks